InventNic (Investment Application for Visual Impairment) / Raja Nurul Afiqah Raja Rosli … [et al.] - Raja Rosli, Raja Nurul Afiqah; Zulkefli, Wan Nur Syazwina; Mohd Ali, Alia Maisarah; Md Shafiee, Nursyaza Liyana; Mohd Sany, Nurliyana ‘Izzati; Abdullah, Nurul Atika Shamila; Mohd Nor, Amirudin (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
In this modern era, investment is a piece of property as well as an object purchased with the intention for producing income and appreciation. As we know, the demand for the mobile application keeps increasing from day to day. However, there aren't many mobile applications that are appropriate for persons with impairments, especially applications for visual impairments. For version impairment person, , investing applications provide a portal to financial independence, allowing them to manage their accounts from home and explore investment alternatives , given their restricted capacity to obtain financial resources to support their expenses. However, the lack of accessibility to these programmes might make it difficult for users to learn how to invest and understand the direction of their investments. With this, we have come up with the idea to make an investment application specifically for visual impairments to generate income through investing in applications that are particularly suitable for them.